Genome Analysis of a New Rhodothermaceae Strain Isolated from a Hot Spring - Goh, Kian Mau; Chan, Kok-Gan; Lim, Soon Wee; Liew, Kok Jun; Chan, Chia Sing; Shamsir, Mohd Shahir; Ee, Robson; Adrian, Tan-Guan-Sheng (Frontiers in Microbiology, 2016)
A bacterial strain, designated RA, was isolated from water sample of a hot spring on Langkawi Island of Malaysia using marine agar. Strain RA is an aerophilic and thermophilic microorganism that grows optimally at 50–60°C and is capable of growing in marine broth containing 1–10% (w/v) NaCl. 16S rRNA gene sequence analysis demonstrated that this strain is most closely related (< 90% sequence identity) to Rhodothermaceae, which currently comprises of six genera: Rhodothermus (two species), Salinibacter (three species), Salisaeta (one species), Rubricoccus (one species), Rubrivirga (one species), and Longimonas (one species). Notably, analysis of average nucleotide identity values indicated that strain RA may represent the first member of a novel genus of Rhodothermaceae. The draft genome of strain RA is 4,616,094 bp with 3,630 protein-coding gene sequences. Its GC content is 68.3%, which is higher than that of most other genomes of Rhodothermaceae. Strain RA has genes for sulfate permease and arylsulfatase to withstand the high sulfur and sulfate contents of the hot spring. Putative genes encoding proteins involved in adaptation to osmotic stress were identified which encode proteins namely Na+/H+ antiporters, a sodium/solute symporter, a sodium/glutamate symporter, trehalose synthase, malto-oligosyltrehalose synthase, choline-sulfatase, potassium uptake proteins (TrkA and TrkH), osmotically inducible protein C, and the K+ channel histidine kinase KdpD. Furthermore, genome description of strain RA and comparative genome studies in relation to other related genera provide an overview of the uniqueness of this bacterium.